Quantitative analysis of crustal deformation, seismic strain, and stress estimation in Iran via earthquake mechanisms - Nemati, Majid; Rashidi, Ahmad; Ezati, Maryam; Derakhshani, Reza (Frontiers in Earth Science, 2024)
This study investigates the variations in stress, strain, and deformation of the Earth's crust in Iran arising from tectonic movements and seismic activities. We employed the Kostrov and Molnar methods to quantify these parameters, focusing on the influence of different zoning techniques on the estimations. Analyzing data from 637 earthquakes (moment magnitudes > 5.5) spanning 1909 to 2016, we determined the directions of maximum pressure, tension, and seismic strain through two primary approaches: comprehensive zoning and individual earthquake analysis. Additionally, we assess horizontal shortening and vertical crustal adjustments. Our methodology involves three distinct strategies: individual earthquake analysis, 1°x1° zoning, and tectonic zoning. The findings demonstrate that the choice of zoning method significantly affects the direction and magnitude of seismic strain estimations. Although both methods identified significant deformations in the Dasht Bayaz and Qaen regions of Eastern Iran, differences between the Kostrov and Molnar methods in estimating seismic strain are observed. The high Zagros region shows signs of crustal thickening, whereas the Zagros foreland exhibits crustal thinning. Intriguingly, Eastern Alborz indicates uplift, and Western Alborz suggests subsidence, offering an alternative view to the conventional tectonic understanding of the Alborz range. These results highlight the critical role of zoning in stress analyses and the disparities between widely used estimation techniques. They underscore the necessity of careful method selection and interpretation in geodynamic studies, particularly in seismically active regions like Iran.